MIS 2021
DOI: 10.20517/2574-1225.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Is mesh fixation in TAPP and TEP still necessary?

Abstract: One of the most serious complications after inguinal hernia repair is still the occurrence of chronic pain. The literature describes rates of severe chronic pain of 3%-6%. Laparo-endoscopic inguinal hernia repair is favored to prevent postoperative pain through a minimally invasive approach and sparing of the layers of tissue covering nerves and vessels in terms of reduced risk of damage to these structures. However, the method of fixation of the mesh is still controversial discussed. The use of these penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Multiples studies in literature have not observed any difference in hernia recurrence between mesh fixation and non-mesh fixation in TEP repair of an inguinal hernia. The mesh fixation with tackers or suture might expose to the risk of entrapment of the nerve and the apparition of chronic postoperative inguinal pain (14)(15)(16). If the fixation is necessary, in exceptional cases, non-traumatic techniques as the use of surgical glue can be a feasible option.…”
Section: Relativesmentioning
confidence: 99%
“…Multiples studies in literature have not observed any difference in hernia recurrence between mesh fixation and non-mesh fixation in TEP repair of an inguinal hernia. The mesh fixation with tackers or suture might expose to the risk of entrapment of the nerve and the apparition of chronic postoperative inguinal pain (14)(15)(16). If the fixation is necessary, in exceptional cases, non-traumatic techniques as the use of surgical glue can be a feasible option.…”
Section: Relativesmentioning
confidence: 99%
“…However, other studies believe that the fixation of mesh is related to nerve injury, foreign body sensation in the operation area and chronic pain. The authors of these studies advocated that the mesh should not be fixed during TEP inguinal hernia repair [ 10 , 11 ]. The aim of this study is systematically analyzed published controlled clinical trials (RCTs) to compare the treatment outcomes of unfixed mesh versus fixed mesh in TEP inguinal hernia repair.…”
Section: Introductionmentioning
confidence: 99%